2022
DOI: 10.1007/s42000-022-00348-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and genotype-phenotype correlations in patients with classical congenital adrenal hyperplasia due to 21-hydroxylase deficiency from southern Poland — experience of a clinical center

Abstract: Purpose The prevalence of CYP21A2 gene variants and genotype-phenotype correlations are variable among populations. The aim of this study was to characterize CYP21A2 gene variants in adult patients with classical congenital adrenal hyperplasia (CCAH) from southern Poland and to analyze genotype-phenotype correlations. Materials/Methods A total of 48 patients (30 women and 18 men) with CCAH were included in the study. Patients were divided into two clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A higher concordance was observed for group C genotypes (70.83%) compared to 2 European studies. In comparison (Table 4), previous studies reported 97-100% concordance for null, 79-96% for A, 46-87% for B, and 58-100% for C genotypes (3)(4)(5)(6)9). One-third of the patients (33.33%) with genotype B were classified as SW-CAH.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A higher concordance was observed for group C genotypes (70.83%) compared to 2 European studies. In comparison (Table 4), previous studies reported 97-100% concordance for null, 79-96% for A, 46-87% for B, and 58-100% for C genotypes (3)(4)(5)(6)9). One-third of the patients (33.33%) with genotype B were classified as SW-CAH.…”
Section: Discussionmentioning
confidence: 70%
“…A complete loss of 21-OH function results in the most severe salt-wasting (SW-CAH) phenotypes, whereas a minimal residual 21-OH production is sufficient to maintain aldosterone homeostasis, resulting in moderate simple virilizing phenotypes (SV-CAH) or mild less-symptomatic nonclassical CAH phenotypes (NC-CAH) (1,2). Numerous studies have examined large nation-based or population-based cohorts of patients around the world to establish genotype-phenotype associations (3)(4)(5)(6)(7)(8)(9). CYP21A2 is located near its pseudogene (CYP21A2P), which is 96% homologous to it.…”
Section: Introductionmentioning
confidence: 99%